Stromal lymphocyte infiltration is associated with tumour invasion depth but is not prognostic in high-grade T1 bladder cancer. (February 2019) - Rouanne, Mathieu; Betari, Reem; Radulescu, Camélia; Goubar, Aïcha; Signolle, Nicolas; Neuzillet, Yann; Allory, Yves; Marabelle, Aurélien; Adam, Julien; Lebret, Thierry
Abstract: Introduction: Assessment of tumour-infiltrating lymphocytes (TILs) can provide important prognostic information in various cancers and may be of value in predicting response to immunotherapy. The objective of the present study was to investigate the association of stromal lymphocytic infiltration with clinicopathological parameters and their correlation with outcomes in patients with high-grade pT1 non–muscle-invasive bladder cancer (NMIBC). Materials and methods: We retrospectively analysed clinical data and formalin-fixed paraffin-embedded (FFPE) tissues of 147 patients with primary high-grade pT1 NMIBC who underwent transurethral resection of the bladder. The stromal TIL density was scored as percentage of the stromal area infiltrated by mononuclear inflammatory cells over the total intratumoural stromal area. The main end-point was correlation with cancer-specific survival (CSS). Results: Median follow-up was 8.2 years (6.1–9.5). Induction Bacillus Calmette–Guérin therapy was undergone by 126 patients (86%). Stromal TILs were high (≥10%) in 82 tumours (56%) and were positively associated with the tumour invasion depth (p = 0.01) and cancers with variant histology (p = 0.01). For the CSS analysis, high (≥10%) versus. low (<10%) stromal TIL hazard ratio (95% confidence interval) was 1.70 (0.7–3.9, p = 0.2). Conclusions: A higher density of stromal TILs was associated with the tumour invasion depth in pT1 NMIBC. The level of TILs was not associated with survival outcomes. These data suggest that tumour aggressiveness is associated with an increased adaptive immune response in pT1 NMIBC. Characterisation of T-cell subtypes along with B-cells may be critical to enhance our knowledge of the host immune response in patients with high-risk NMIBC. Highlights: Lymphocytic infiltration significantly increases with tumour invasion depth in primary untreated pT1 bladder cancer. A higher density of lymphocytic infiltration is not associated with better outcomes. These data suggest that the antitumour immune response is different in high-grade pT1 non-NMIBC as opposed to numerous findings in MIBC. Characterisation of T-cells and B-cells responses is critical to enhance our knowledge of antitumour immunity in patients with high-risk non-NMIBC.